Polyterthiophenes cross-linked with terpyridyl metal complexes for molecular architecture of optically and electrochemically tunable materials - Wagner, Michal (2022)
Novel conductive polymer-based metal complexes were electrochemically synthesized and characterized in relation to (spectro)electrochemical stimuli. Particularly, we focused our attention on terthiophenes functionalized with terpyridine groups, along with Fe2+ cations present during electrochemical synthesis. The resultant electroactive films are coherent, robust, and exhibit mixed absorption profiles upon electrochemical doping, characteristic for both polyterthiophenes and metal-ligand transitions. At certain oxidation potentials, the formation of radical cation and also dication states were observed. The latter, influence the optical transitions related to metal centers, and can reversibly be everted by switching to lower potentials. Furthermore, the polymer “cross-linking metal” can be removed from the structure, which we obtained by partial exchange of Fe2+ with Cu2+ and Zn2+ cations. The conducted cation exchange studies however elucidate the complexity and difficulty of such an approach. With future electropolymerization “strategies” we are expecting to extend film stability during application of relatively high potentials, as well as in the interim of cation exchange.